Preliminary biocompatibility investigation of magnetic albumin nanosphere designed as a potential versatile drug delivery system - Estevanato, Luciana Landim Carneiro (2011)
Background: The magnetic albumin nanosphere (MAN), encapsulating maghemite nanoparticles, was designed as a magnetic drug delivery system (MDDS) able to perform a variety of biomedical applications. It is noteworthy that MAN was efficient in treating Ehrlich’s tumors by the magnetohyperthermia procedure. Methods and materials: In this study, several nanotoxicity tests were systematically carried out in mice from 30 minutes until 30 days after MAN injection to investigate their biocompatibility status. Cytometry analysis, viability tests, micronucleus assay, and histological analysis were performed. Results: Cytometry analysis and viability tests revealed MAN promotes only slight and temporary alterations in the frequency of both leukocyte populations and viable peritoneal cells, respectively. Micronucleus assay showed absolutely no genotoxicity or cytotoxicity effects and histological analysis showed no alterations or even nanoparticle clusters in several investigated organs but, interestingly, revealed the presence of MAN clusters in the central nervous system (CNS). Conclusion: The results showed that MAN has desirable in vivo biocompatibility, presenting potential for use as a MDDS, especially in CNS disease therapy.